Reduction in exhaled nitric oxide immediately after methacholine challenge in asthmatic children. Issue 9 (1st September 2002) - Piacentini, G L; Bodini, A; Peroni, D G; Del Giudice, M Miraglia; Costella, S; Boner, A L
Abstract : Background: The measurement of exhaled nitric oxide (NO) has recently been proposed as a useful technique for the evaluation of airway inflammation in asthma. The purpose of this study was to determine the effect of methacholine bronchial provocation on the levels of exhaled NO in asthmatic children. Method: Exhaled NO was measurement immediately before and after methacholine provocation in 51 children with mild to moderate asthma. Results: A significant decrease occurred in the level of exhaled NO (p<0.0001) after methacholine bronchial provocation which was not correlated with the percentage fall in forced expiratory volume in 1 second (FEV1 ). Conclusions: The methacholine test should not be used immediately before measurement of exhaled NO in children with asthma.